Guru Berkualitas: Esensi Pendidikan Bermutu - Hasanah, Indah Maulidia; Asbari, Masduki; Wardah, Hani (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to solve educational problems in order to create an extraordinary young generation, one of which is improving the quality of teachers in Indonesia. To be a quality teacher, you must have extensive experience and knowledge so that students do not get bored or bored in the learning process being implemented. The research data taken from this research is a descriptive research method, namely to create a systematic, factual and accurate description, picture or painting of the facts, characteristics and relationships between the phenomena being investigated. with regard to teacher quality, there are 3 dimensions that constitute the competence of educational staff, namely as follows: 1) Personal Competence, namely that a teacher must have a solid personality that is worthy of emulation; 2) Professional competence, namely a teacher must have broad, in-depth knowledge of the field of study being taught; and 3) Social competence, namely that a teacher must be able to communicate well with his students, fellow teachers and the wider community